2012
DOI: 10.1063/1.4739766
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-activated Raman spectra of cubic rocksalt-type Li(1−x)/2Ga(1−x)/2MxO (M = Mg, Zn) alloys

Abstract: Cation order-disorder phase transitions in LiGaO 2 : Observation of the pathways of ternary wurtzite under high pressure Disorder-activated phonon behaviors of the cubic rocksalt-type semiconductor alloy Li (1Àx)/2 Ga (1Àx)/2 M x O (M ¼ Mg, Zn) prepared by high-pressure and high-temperature method has been studied by Raman scattering analysis. The LO Raman phonon in Li (1Àx)/2 Ga (1Àx)/2 M x O was found to exhibit a distinct two-mode behavior. The compositional dependence of Raman frequency, peakwidth, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
2
5
0
Order By: Relevance
“…Additionally, new bands appear in the Raman spectra at frequencies between the CdSe and the CdS LO frequencies. This reflects the breaking of the translational invariance of the lattice in a random alloy, which lifts the q = 0 Raman selection rule, thereby making previously forbidden vibrations afar from the LO phonon frequency Raman active. Additionally, nonlongitudinal alloy vibrations incorporating both anions could be Raman active and result in additional peaks, as observed for CdSe 0.5 S 0.5 alloys and confirmed by DFT calculations . These effects agree with published studies on alloyed semiconductors and isotope mixtures.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, new bands appear in the Raman spectra at frequencies between the CdSe and the CdS LO frequencies. This reflects the breaking of the translational invariance of the lattice in a random alloy, which lifts the q = 0 Raman selection rule, thereby making previously forbidden vibrations afar from the LO phonon frequency Raman active. Additionally, nonlongitudinal alloy vibrations incorporating both anions could be Raman active and result in additional peaks, as observed for CdSe 0.5 S 0.5 alloys and confirmed by DFT calculations . These effects agree with published studies on alloyed semiconductors and isotope mixtures.…”
supporting
confidence: 82%
“…This indicates a very homogeneous distribution of S and Se for this composition, whereas other S/Se ratios result in an increased asymmetry and a subsequent increase of the fwhm, in agreement with the expectations for homogeneous alloys. 24,26 Size variations generally also result in a broadened Raman peak due to a varying phonon confinement. We expect the contribution of this to be small for our samples due to weak confinement and rather narrow distributions.…”
mentioning
confidence: 99%
“…Raman spectroscopy follows the longitudinal and transverse vibrations of Zn and O-sublattices, which could be influenced by heavy dopant incorporation and oxygen rearrangement. Concerning the right-hand shoulder at the E 2 low phonon (see Figure 2), similar results were obtained in Li et al 21 where the authors observed a lowfrequency shoulder at the E 2 low phonon caused by the substitutional disorder, whose intensity increased with increasing Ag concentration in the ZnO lattice; this effect could also be presumed for Au ions, however it was shown that Au is not entering subsitutional positions in wurtzite structure to the higher extent.22 Thus this phenomenon is more likely connected to selection rules relaxation. Moreover, all investigated cuts exhibited intense phonon bands E 1 (LO) and A 1 (LO) simultaneously with the right-hand shoulder at the E 2 low phonon.…”
Section: T a B L Esupporting
confidence: 89%
“…Based on the common knowledge that isomorphic substitution may cause Raman shifting, such secondary Raman peak can be inferred from existing phenomenon. If the secondary Raman peak is on the left side (lower frequency direction) of the main OHstretching peak, substitution should be relevant to light elements substituted by heavy elements, and vice versa (Nagashima, M. et al 2021;Lei, L. et al 2012;Langer, K. and Raith, M. 1974; Heuss-Aßbichler, S. and Fehr, K.T. 1997).…”
Section: Discussionmentioning
confidence: 99%